2023
DOI: 10.1186/s12955-023-02152-8
|View full text |Cite
|
Sign up to set email alerts
|

Applying multidimensional computerized adaptive testing to the MSQOL-54: a simulation study

Abstract: Background The Multiple Sclerosis Quality of Life-54 (MSQOL-54) is one of the most commonly-used MS-specific health-related quality of life (HRQOL) measures. It is a multidimensional, MS-specific HRQOL inventory, which includes the generic SF-36 core items, supplemented with 18 MS-targeted items. Availability of an adaptive short version providing immediate item scoring may improve instrument usability and validity. However, multidimensional computerized adaptive testing (MCAT) has not been pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
0
0
Order By: Relevance
“…The study also found that when variable length stopping rules are used (SE<0.30; SE<0.50; SE<0.70), ability estimation can be made with 84%-90% fewer items than the original scale. This finding is in parallel with the advantage of the following ratios in the number of items: the rate of 73.3% was reached as a result of the study of Gardner et al (2004); the rates of 36%-65% reached as a result of the study of Smits et al (2011); the 50.86% rate reached as a result of Aybek and Demirtaşlı's ( 2017) study; the rate of 75% obtained in the study of Gibbons et al (2016); the rate of 67% obtained in the study by Stochl et al (2016); the 50%-85% rates obtained in the study by Petersen et al (2016); the 30%-71% rates obtained in the study by Choi and McClenen (2020); the rate of 75% obtained in the study by Harrison et al (2020); the 50%-63% rates obtained in the study by Yasuda et al (2021); the 62%-96% rates obtained in the study by Liu et al (2022); the rate of 78% obtained in the study by Giordano et al (2023). In the studies conducted by Smits et al (2011) andAybek andDemirtaşlı (2018), it can be said that the low ratio in test lengths is because there is a more limited pool of items compared to other studies.…”
Section: Discussionmentioning
confidence: 93%
“…The study also found that when variable length stopping rules are used (SE<0.30; SE<0.50; SE<0.70), ability estimation can be made with 84%-90% fewer items than the original scale. This finding is in parallel with the advantage of the following ratios in the number of items: the rate of 73.3% was reached as a result of the study of Gardner et al (2004); the rates of 36%-65% reached as a result of the study of Smits et al (2011); the 50.86% rate reached as a result of Aybek and Demirtaşlı's ( 2017) study; the rate of 75% obtained in the study of Gibbons et al (2016); the rate of 67% obtained in the study by Stochl et al (2016); the 50%-85% rates obtained in the study by Petersen et al (2016); the 30%-71% rates obtained in the study by Choi and McClenen (2020); the rate of 75% obtained in the study by Harrison et al (2020); the 50%-63% rates obtained in the study by Yasuda et al (2021); the 62%-96% rates obtained in the study by Liu et al (2022); the rate of 78% obtained in the study by Giordano et al (2023). In the studies conducted by Smits et al (2011) andAybek andDemirtaşlı (2018), it can be said that the low ratio in test lengths is because there is a more limited pool of items compared to other studies.…”
Section: Discussionmentioning
confidence: 93%